Concept analysis of self-efficacy among schizophrenia - Rahmawati, Ashri Maulida; Sawitri, Dian Ratna; Dwidiyanti, Meidiana; Rahman, Ainun Najib Febrya (Universitas Aisyah Pringsewu, 2020)
The concept of self-efficacy is a core development concept of social cognitive theory. Self-efficacy is needed by schizophrenia patients to overcome problems. The initiation aims are to analyze concepts and clarify the conceptual meaning of self-concepts for schizophrenic patients. Walker and Avant's concept analysis procedure was used in this administration. A Literature review was carried out using online databases such as Science Direct, PubMed, EBSCO, and Proquest with the keywords